Improvements in the cooling capacity and the COP of a transcritical CO2 refrigeration plant operating with a thermoelectric subcooling system. (5th June 2019) - Astrain, D.; Merino, A.; Catalán, L.; Aranguren, P.; Araiz, M.; Sánchez, D.; Cabello, R.; Llopis, R.
Highlights: New subcooling system equipped with thermoelectric modules. Decrease of energy consumption in vapour compression plants working with CO2. Improvement up to 33 % in the cooling capacity and up to 24 % in the COP. Computational tool for the optimization of a CO2 vapour compression system combined with thermoelectric subcooler. Abstract: Restrictive environmental regulations are driving the use of CO2 as working fluid in commercial vapour compression plants due to its ultra-low global warming potential (GWP100  = 1) and its natural condition. However, at high ambient temperatures transcritical operating conditions are commonly achieved causing low energy efficiencies in refrigeration facilities. To solve this issue, several improvements have been implemented, especially in large centralized plants where ejectors, parallel compressors or subcooler systems, among others, are frequently used. Despite their good results, these measures are not suitable for small-capacity systems due mainly to the cost and the complexity of the system. Accordingly, this work presents a new subcooling system equipped with thermoelectric modules (TESC), which thanks to its simplicity, low cost and easy control, results very suitable for medium and small capacity plants. The developed methodology finds the gas-cooler pressure and the electric voltage supplied to the TESC system that maximizes the overall COP of the plant taking into account the ambient temperature, the number of thermoelectric modules used and the thermal resistance of the heat exchangers included in the TESC. The obtained results reveal that, with 20 thermoelectric modules, an improvement of 20% in terms of COP and of 25.6% regarding the cooling capacity can be obtained compared to the base cycle of CO2 of a small cooling plant refrigerated by air. Compared to a cycle that uses an internal heat exchanger IHX, the improvements reach 12.2% and 19.5% respectively.